2000
DOI: 10.1126/science.288.5466.661
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Odds of Large Earthquakes Near Istanbul: An Interaction-Based Probability Calculation

Abstract: We calculate the probability of strong shaking in Istanbul, an urban center of 10 million people, from the description of earthquakes on the North Anatolian fault system in the Marmara Sea during the past 500 years and test the resulting catalog against the frequency of damage in Istanbul during the preceding millennium. Departing from current practice, we include the time-dependent effect of stress transferred by the 1999 moment magnitude M = 7.4 Izmit earthquake to faults nearer to Istanbul. We find a 62 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
315
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(334 citation statements)
references
References 29 publications
14
315
0
5
Order By: Relevance
“…Recent studies conducted after the 1999 Kocaeli (Mw=7.4) and Düzce (Mw=7.2) earthquakes indicate (assuming that the stress regime in the Marmara Sea remains unchanged) about 65% probability for the occurrence of an Mw>=7.0 magnitude earthquake effecting Istanbul Parsons [15]. The association of earthquakes between 1500 to present with the segmentation proposed for the North Anatolian Fault in the Marmara Region is given in Table 1.…”
Section: Seismicitymentioning
confidence: 99%
“…Recent studies conducted after the 1999 Kocaeli (Mw=7.4) and Düzce (Mw=7.2) earthquakes indicate (assuming that the stress regime in the Marmara Sea remains unchanged) about 65% probability for the occurrence of an Mw>=7.0 magnitude earthquake effecting Istanbul Parsons [15]. The association of earthquakes between 1500 to present with the segmentation proposed for the North Anatolian Fault in the Marmara Region is given in Table 1.…”
Section: Seismicitymentioning
confidence: 99%
“…This mechanism has been invoked, for example, to explain the progressive failure of the North Anatolian fault between 1939 and 1999 (e.g., Stein et al, 1997), and to calculate future seismic hazards along the fault (e.g., Hubert-Ferrari et al, 2000;Parsons et al, 2000). In general, after a major earthquake, areas where stress has increased are favored areas for aftershocks and/or subsequent mainshocks occur (Harris, 1998).…”
Section: The Yuli Rupture and The Longitudinal Valley Faultmentioning
confidence: 99%
“…This lobe is 40 km to the west of the mainshock, where the M W 6.5 Big Bear earthquake struck 2.5 h afterwards (Stein 1999). In Turkey, the 1999 M W 7.4 Izmit earthquake was followed by the M W 7.1 Düzce earthquake that is a triggered event by the former about three months later (Parsons et al 2000). In the 2008 Wenchuan event, some faults to the south of the Longmenshan fault exhibited increased transferred Coulomb stress (Parsons et al 2008), especially the Ya'an thrust and Xianshuihe fault, which were shown to have distinctly greater changes in Coulomb stress than other faults.…”
Section: Introductionmentioning
confidence: 99%
“…A big earthquake can cause stresses on faults to decrease or increase, and it also alters stresses elsewhere (Parsons et al 2000). Earthquakes are more prone to being observed in regions of increased stress, while they are less seen where off-fault stresses decrease (Stein 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation